2021
DOI: 10.1039/d1ra06902k
|View full text |Cite
|
Sign up to set email alerts
|

Co(ii), Ni(ii), Cu(ii) and Cd(ii)-thiocarbonohydrazone complexes: spectroscopic, DFT, thermal, and electrical conductivity studies

Abstract: New and stable coordinated compounds have been isolated in a good yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 98 publications
5
15
0
Order By: Relevance
“…As a consequence, the DTA peaks with T min at 255 °C (strong endothermic) and T max at 362 °C (weak exothermic), 436 °C (strong exothermic), 526 °C (weak exothermic), and 642 °C (weak exothermic) associated with the multistep thermal decomposition processes are observed. The leftover masses correspond to the formation of CuO as the possible final residue for all three complexes. , Comparable thermal behavior has been reported in the literature, showing the removal of lattice H 2 O, Cl 2 , and CO 2 gases from allied chloride-/carboxylate-containing metal complexes. …”
Section: Resultssupporting
confidence: 56%
“…As a consequence, the DTA peaks with T min at 255 °C (strong endothermic) and T max at 362 °C (weak exothermic), 436 °C (strong exothermic), 526 °C (weak exothermic), and 642 °C (weak exothermic) associated with the multistep thermal decomposition processes are observed. The leftover masses correspond to the formation of CuO as the possible final residue for all three complexes. , Comparable thermal behavior has been reported in the literature, showing the removal of lattice H 2 O, Cl 2 , and CO 2 gases from allied chloride-/carboxylate-containing metal complexes. …”
Section: Resultssupporting
confidence: 56%
“…The spectrum of the ligand (Figure 1) displays three characteristic bands at 3374, 3324, and 3308 cm À1 , assignable to ν as (NH 2 ), ν sy (NH 2 ), and ν(NH), respectively. [37,38] Moreover, the δ(NH 2 ) and δ(NH) ligand bands locate at 1595 and 1446 cm À1 , respectively. [39][40][41] Also, the ligand spectrum exhibits three remarkable bands at 1684, 683, and 606 cm À1 , ascribed to ν(C=O), δ(C=O), and γ(C=O), respectively.…”
Section: Infrared Spectral Studiesmentioning
confidence: 99%
“…[45,46] Meanwhile, the stretching vibrations of aromatic ÀCH and ÀCH 2 bands are observed at 3050 and 2982, 2920 cm À1 , respectively. [37,47] The ligand spectrum reveals a medium characteristic band at 1446 cm À1 , attributed to ÀCH 2 deformation [44,48] (Table 2).…”
Section: Infrared Spectral Studiesmentioning
confidence: 99%
“…DFT has been proved to be best approach to investigate theoretically structure-property relationship for a compound as it shows excellent solution when both accuracy and computational time are taken in account [11] . FMO analysis provides the parameters for calculating the FMO energy gap which is used for describing the electronic structure of the compound [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a series of copper and nickel complexes of thiosemicarbazones having heterocyclic moiety has been synthesised and found that the nature of heteroatomic ring attached to them can considerably influence the biological activities of these complexes [8] , [9] , [10] , [11] . These ligands and their complexes have been extensively studied exploring their biological properties, including antibacterial, antimalarial, antiviral, antioxidant, cytotoxic and antineoplastic [12] , [13] , [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%